Atividade imuno-inflamatória de ovalbumina : papel de células e mediadores do sistema imune intestinal na migração de eosinófilos - Feitosa, Regina Fátima Gonçalves (2003)
Rats are commonly used in anaphylaxis models, mainly in the intestinal anaphylaxis; whose mechanisms are very complex and are not clearly defined. The objectives of this study were: a) to investigate the pro-inflammatory effect of ovalbumin (OVA) by the hind paw edema model in sensitized rats; b) to identify the mediators involved in this immune-inflammatory reaction; and c) to evaluate the involvement of the cells and mediators of the intestinal immune system, in the pathophysiology of the intestinal hypersensitivity induced by OVA. The pharmacological modulation of hind paw edema was studied in Wistar rats immunized with OVA (30pg, with AI(OH)3; i.p), 14 to 18 days prior to the evaluation; using animais sham-sensitized with aluminum hydroxide as Controls. The paw volumes were measured prior to the antigenic stimuli and at 1, 2, 3 and 4 hours after the intraplantar injection of lOpg/paw of OVA. The subcutaneous applications of dexamethasone, diphenhydramine, cyroheptadine, chlorpromazine or methysergide significantly inhibited (p<0.05) the allergic paw reaction. NDGA, indomethacin, MK-886, WEB 2086, ketotifen and meclizine failed to block this reaction; as also thalidomide and pentoxifylline. The intestinal lamina própria cells (LPIC) were isolated from rats pre-sensitized as described, by enzymatically digesting cut and washed small intestine. The isolated cells were washed and incubated with 10pg of OVA for 60 min; followed by a subsequent incubation for 2 hours in Dulbecco médium. The supernatant (Sup) from 107 cells/mL was tested in the protocol for peritoneal cellular migration. Pharmacological mediators, or PBS, were injected 30 min before stimulus. The Sup was incubated with the monoclonal antibodies (MoAB) for 30 min before the administration.